(untitled) (Raparin Journal of Humanities (RJH), 2025)
The purpose of this research to know the effect of the school entourage in the formation of students’ character and know the effect of the physical entourage and identify the effect of the social entourage as well as the importance of identifying the effect of the school entourage in the formation of students’ character in the preparatory grade of the faculty for both genders. This phenomenon is a kind of human behavior when some students are exposed to problems in society and the school entourage related to interaction and cooperation. The approach used in this research was the Analytical descriptive. The results of the study showed a positive significance. the value of the correlation coefficient was between the two variables (>0.501) and at the level of significance was) > 0.05) and we conclude higher of the levels of interest in the school entourage, the higher the levels of students’ character by (50.1%). There was a positive statistically significant correlation between the physical character dimension of the school character variable and the students’ entourage variable, as the value of the correlation coefficient and the physical environment and the students’ personality variable equal to (>0.413 ). The level of assumed statistical significance by the researcher (>0.05) and confirms that the higher the levels of interest in the physical entourage. the Physical entourage levels and variety of students’ character by (41.3%), there was a significant correlation with positive statistical significance between the dimension of the social entourage from the variable school entourage and the variable of students’ character, as the value of the correlation coefficient between the social environment and the variable of students’ character (0.521) and at the level of statistical significance assumed by the researcher (>0.05) and this was approved that the higher the social character levels causing an increase the character of students by (52.1%).